Global Education in the Spanish Educational Policies of Elementary and Primary Education: Utopia or Reality? - Santamaría-Cárdaba, Noelia; Martínez-Scott, Suyapa (Acta Paedagogica Vilnensia, 2023)
Global education is becoming increasingly relevant at the international level, since forming critical citizens who act against inequalities and in favor of sustainable development is undoubtedly the path to where social transformation should be headed. The role of formal education in developing global competence in students is undeniable, which makes it necessary to include it in educational policies. This study uses a qualitative perspective since a documentary analysis is made to investigate the treatment of global education in the current educational curricula in Spain for Elementary Education and Primary Education. The results show deficiencies when dealing with several key issues for the correct teaching of global education.